Vivenciando uma prática de ensino/estágio curricular supervisionado na formação inicial do educador de Língua Espanhola - Bráñez, Leonor Nora Fabián (2014)
This research aimed to critically understand how the organization of the Practice Teaching/Supervised Curricular Training of Foreign Language (PE/ECS LE) in an undergraduate degree in Letters: Portuguese-Spanish enables the articulation between theory and practice and developing critical and reflective future teachers of Spanish. The interest in this issue began with my experiences as a teacher of Spanish language in a Higher Education Institution (IES) in a multicultural area in the northern region of the country, which enabled me to identify complex issues in relation to the initial training of LE teachers. The PE/ECS is a curricular component that provides the basis of the profession in practice pre-service. It is fundamental in linguistics and pedagogical training of the future teacher of Spanish as a Foreign Language. PE/ECS I - Observation and PE / ECS II - Regency in Spanish, theoretical and practical curriculum components discussed in this research, are sequential, and occurred on the 7th and 8th semesters of the course, in 2009. Starting from the socio-historical-cultural vision, according to Vygotsky ([1934] 2011), and the concepts of dialogism and polyphony discussed by Bakhtin/Voloshinov ([1929] 2003), this work is grounded in dialectical and dialogical conceptions of language learning for development. It is considered the Applied Linguistics and its relationship with foreign language teaching (Pennycook, 2006), sociodiscursive interactionist perspective (Bronckart, 2009), to discuss the actions of language, thematic content, texts and discourses and discursive social practices (Dolz and Schneuwly, 2004). As for critical thinking, this research relied on Smyth (1992), critical pedagogy Freire (1970.1996), and the discussions and contributions of Magalhães (1990, 2007, 2011), Ninin (2002, 2010), Magalhães and Fidalgo (2007, 2011) Liberali (2008, 2012). The results showed us that discussions partially allowed the articulation between theory and practice and the development of critical and reflective training of students. Students reflect more on the context of school than on teaching and learning. Also pointed out that the curriculum component PE/ECS I Observation constitutes in a place where PE/ECS II - Regency can be organized